2004
DOI: 10.1111/j.1369-7625.2004.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Quality Information for Patients: development and preliminary validation of a new instrument to improve the quality of written health care information

Abstract: Background Despite the recent focus on improving the quality of patient information, there is no rigorous method of assessing quality of written patient information that is applicable to all information types and that prescribes the action that is required following evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 31 publications
2
184
0
6
Order By: Relevance
“…Alguns autores relatam, entretanto, que quando mal confeccionadas dificultam o entendimento e a compreensão dos usuários (5) . O material educativo deve ser ter linguagem acessível, uma vez que quanto menor o nível de leitura, mais provável que seja lido por grande parte do público-alvo (6) . Além disso, dado o avanço tecnológico, observa-se cada vez mais a possibilidade de disseminação de informações em saúde em mídias digitais, uma vez que panfletos e folhetos escritos são limitados em relação ao acesso (7) .…”
Section: Introductionunclassified
“…Alguns autores relatam, entretanto, que quando mal confeccionadas dificultam o entendimento e a compreensão dos usuários (5) . O material educativo deve ser ter linguagem acessível, uma vez que quanto menor o nível de leitura, mais provável que seja lido por grande parte do público-alvo (6) . Além disso, dado o avanço tecnológico, observa-se cada vez mais a possibilidade de disseminação de informações em saúde em mídias digitais, uma vez que panfletos e folhetos escritos são limitados em relação ao acesso (7) .…”
Section: Introductionunclassified
“…12,18 Graber et al 19 evaluated 50 health related websites and found the average reading level to be about 10th grade (equivalent to a reading age of 15-16 years), despite the fact the level of reading comprehension is lower in most patient populations. The top ranking websites we identified for quality and technological information (Table 3) all had SMOG ratings far greater than 10, the level most people would be expected to understand.…”
Section: J O U R N a L O F T H E R O Y A L S O C I E T Y O F M E D Imentioning
confidence: 99%
“…Pemberian terapi gabungan (aktif dan pasif) ini didasarkan pada temuan sebelumnya oleh Moult et al (2004) bahwa informasi kesehatan yang diterima oleh seorang pasien bisa terlupakan dalam beberapa menit setelah mereka mendapatkan informasi, karena itu diperlukan booklet supaya penderita bisa mengulang di rumah apa yang telah dibicarakan sebelumnya dengan perawat. Penderita TB yang datang ke Puskesmas yang masuk kedalam kelompok intervensi diberikan konseling tentang masalah psikososial yang mereka hadapi, kemudian diberikan booklet yang berisi tentang cara-cara mengatasi masalah psikososial yang biasa dialami penderita TB.…”
Section: Pembahasanunclassified